Prior Entrepreneurial Exposure and Action of Women Entrepreneurs: Exploring the Moderation Effects of Entrepreneurial Competencies in a Developing Country Context - Botha, Melodi (Frontiers in Psychology, 2020)
While the differences between men and women with regard to entrepreneurial activity is well-acknowledged, few scholars have explored models explaining the differences through an objectivist lens. This research addresses this gap by investigating the relationship between prior entrepreneurial exposure and entrepreneurial action, moderated by entrepreneurial competencies. This paper draws from two psychology theories to develop and test a three-factor model of entrepreneurial action. The structuration theory formulates a theoretical model which explains how an entrepreneurs’ interaction with their environment, and their concomitantly learned behavioral scripts (i.e. entrepreneurial competencies), impact a newly formulated typology of entrepreneurial gestation activities based on the mindset theory of action phases. Furthermore, the entrepreneurial competencies in this paper are drawn from a systematic framework of entrepreneurship competency development which categorizes entrepreneurial competencies into 1). Entrepreneurial attitudes and personal characteristics and 2). Entrepreneurial motives. By dividing entrepreneurial action into a predecisional, preactional and actional phase, a novel approach is used in taking the context of the entrepreneurial process into account. It is proposed that prior entrepreneurial exposure is a significant and positive predictor of future entrepreneurial action in the predecisional and preactional phases. However, once entering the actional phase, this factor is no longer important as women entrepreneurs have crossed the entrepreneurial Rubicon. The sample consists of South African entrepreneurs of which 346 women entrepreneurs and a sample of 804 male entrepreneurs are used to compare the results of the first hypothesis. Structural Equation modelling (SEM) is used to model the relationship between prior entrepreneurial exposure and entrepreneurial action. Results confirm that prior entrepreneurial exposure in the form of role models, entrepreneurial parents or any other form of exposure to entrepreneurship before starting a business is particularly important to encourage women to pursue business start-up (action). Furthermore, the development of certain entrepreneurial competencies is crucial for improving the strength of the relationship between prior entrepreneurial exposure and entrepreneurial action for women entrepreneurs. These results have important implications for women entrepreneurs, educators as well as entrepreneurship models which have been traditionally male-dominated.